2017
DOI: 10.3892/etm.2017.4202
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pericardial fluid T-cells and related inflammatory cytokines in patients with chronic heart failure

Abstract: Pericardial fluid, as a biochemical indicator of heart status, directly indicates pathological alteration to the heart. The accumulation of pericardial fluid can be attributed to an underlying systemic or local inflammatory process. However, the pericardial fluid expression of cellular surface markers, as well as several cytokines in chronic heart failure (CHF), remain unclear. In order to evaluate these issues further the pericardial fluid expression of several cytokines and the surface expression of activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Pericardial fluid could also be used as a signal to evaluate cardiac pathological changes ( Xiang et al, 2013 ; Foglio et al, 2015 ). A large amount of T cell infiltration and increased cytokines could be observed in the pericardial fluid of patients with chronic heart failure, leading to changes in the myocardial structural matrix and cause myocardial cell apoptosis that results in inflammation, which reflects T cell activation ( Iskandar et al, 2017 ). The tissue origins of PFCs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial fluid could also be used as a signal to evaluate cardiac pathological changes ( Xiang et al, 2013 ; Foglio et al, 2015 ). A large amount of T cell infiltration and increased cytokines could be observed in the pericardial fluid of patients with chronic heart failure, leading to changes in the myocardial structural matrix and cause myocardial cell apoptosis that results in inflammation, which reflects T cell activation ( Iskandar et al, 2017 ). The tissue origins of PFCs remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced proinflammatory cytokines secreted from these immune cells may contribute to the pathogenesis of myocardium dysfunction and the syndrome of HF [ 26 , 27 ]. Multiple clinical reports have revealed that patients with HF have elevated levels of inflammatory cytokines, such as TNF- α , IL-1 β , MCP-1, and IL-8 in circulation and myocardial tissues [ 28 , 29 ]. Increased circulating level of TNF- α appears to be associated with the deterioration of left ventricular function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the content of PF changes in pathological situations, PF content can be a useful tool to detect pathological changes in the heart. 13,14 The porcine pericardium is commonly used in various applications, because of its high biocompatibility. It is FDA-approved for use in including stent covers, prosthetic valve materials, and the repair of soft tissue defects.…”
Section: Introductionmentioning
confidence: 99%
“…PF contents and amounts are used for diagnosing heart diseases. Because of the content of PF changes in pathological situations, PF content can be a useful tool to detect pathological changes in the heart 13,14 …”
Section: Introductionmentioning
confidence: 99%